Principles of failure analysis [videorecording] : failures of pressure vessels (West Conshohocken, Pennsylvania, United States : ASM International, 1992)
Covers pressure vessels and piping, causes of failure, operating temperatures, procedures for failure analysis, metallurgical discontinuities, stress-raisers, effects of fabrication practices, rimmed steel, pressure vehicles of composite materials, composites, composite lining application, plug weld, service related failures, residual stresses, applied stresses, brittle fractures, ductile fractures, creep and stress rupture, and fatigue failures.